The Concept of Islamic Humanistic Education - Siti Rahmah; Umar Fauzan; Noor Malihah (Budapest International Research and Critics University, 2022)
Humanistic education is an education that the Prophet has taught to humans, but over time, many figures, not only Islamic figures but also western figures, have studied this humanistic education. The study of this research is qualitative using literature. The literature collected comes from books and national and international journals related to humanistic education in general and Islam. After the literature is collected, the researcher conducts an in-depth study by selecting the relevant literature to discuss this study and analyze data from the literature obtained. From the results of the research conducted, the researcher got several findings in the study where humanistic education is closely related to humanizing humans, so the main thing to do is pay attention to physiological development, improve mindsets, hearts, emotions, and social aspects with the guidance of the Qur'an and hadith.